2018
DOI: 10.1111/vsu.12952
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical analysis of suture attachment methods in toggle suture constructs

Abstract: Objective To determine the effect of the method used to attach OrthoFiber #5 to a 1/8‐in Securos toggle rod on the mechanical properties of the resulting construct. Study design Prospective bench top mechanical analysis. Sample population One hundred twenty‐eight OrthoFiber #5‐toggle rod suture constructs. Methods Toggle–suture constructs (groups A‐H) were prepared by using 8 methods to attach OrthoFiber #5 to a 1/8‐in toggle rod (n = 16 constructs/group). A servohydraulic materials‐testing machine was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mechanical characteristics of different sutures used in HTS constructs and methods of suture attachment to the toggle have been evaluated by several investigators 29‐32 . Braided ultrahigh– molecular‐weight‐polyethylene (UHMWPE) has been demonstrated to be mechanically superior to monofilament nylon leader because of its higher tensile strength, increased stiffness, and greater resistance to elongation 30‐32 .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical characteristics of different sutures used in HTS constructs and methods of suture attachment to the toggle have been evaluated by several investigators 29‐32 . Braided ultrahigh– molecular‐weight‐polyethylene (UHMWPE) has been demonstrated to be mechanically superior to monofilament nylon leader because of its higher tensile strength, increased stiffness, and greater resistance to elongation 30‐32 .…”
Section: Introductionmentioning
confidence: 99%
“…In canine cadaveric studies, braided high tensile strength sutures, as used in this study, have shown superior in vitro mechanical properties with better mechanical predictability over monofilament sutures. [20][21][22][23][24][25][26] In clinical cases, one would expect this to translate into less suture breakage and a lower luxation rate when multifilament suture is chosen over monofilament. The reported reluxation rate with TightRope is 5.8%, lower than the 11 to 25% rate previously reported with monofilament repairs.…”
Section: Discussionmentioning
confidence: 99%